2020
DOI: 10.1073/pnas.2015026117
|View full text |Cite
|
Sign up to set email alerts
|

Human Argonaute2 and Argonaute3 are catalytically activated by different lengths of guide RNA

Abstract: RNA interfering is a eukaryote-specific gene silencing by 20∼23-nucleotide (nt) microRNAs and small interfering RNAs that recruit Argonaute proteins to complementary RNAs for degradation. In humans, Argonaute2 (AGO2) has been known as the only slicer while Argonaute3 (AGO3) barely cleaves RNAs. Therefore, the intrinsic slicing activity of AGO3 remains controversial and a long-standing question. Here, we report 14-nt 3′ end-shortened variants of let-7a, miR-27a, and specific miR-17–92 families that make AGO3 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…Such short RNAs would be quite susceptive to cellular RNases because they are too short to fold into a hairpin structure or form a stable duplex. Supporting this idea, my recent study showed that transfection of an unmodified, 14 nt guide RNA into HEK293T cells failed to activate AGO3 (Park et al, 2020), probably due to single-stranded RNA degradation by the cellular RNases (Lima et al, 2012). However, when the same 14 nt single-stand was heavily modified, it loaded onto AGO3 and converted it to an active slicer.…”
Section: Possible Pathways Of Tiny Rna Biogenesis Direct Loading Of Tyrnas Into Agosmentioning
confidence: 97%
See 3 more Smart Citations
“…Such short RNAs would be quite susceptive to cellular RNases because they are too short to fold into a hairpin structure or form a stable duplex. Supporting this idea, my recent study showed that transfection of an unmodified, 14 nt guide RNA into HEK293T cells failed to activate AGO3 (Park et al, 2020), probably due to single-stranded RNA degradation by the cellular RNases (Lima et al, 2012). However, when the same 14 nt single-stand was heavily modified, it loaded onto AGO3 and converted it to an active slicer.…”
Section: Possible Pathways Of Tiny Rna Biogenesis Direct Loading Of Tyrnas Into Agosmentioning
confidence: 97%
“…Therefore, few transcripts encompass the perfectly complementary sequence, which could explain why only a few mRNAs are cleaved by AGO2 with mature miRNAs. My recent study discovered that loading 14 nt specific tyRNA catalytically activates AGO3, while reducing the slicing activity of AGO2 compared to that of their mature miRNAs ( Park et al, 2020 ). The sequence fully complementary to a 14 nt cityRNA appears every 67 million nucleotides (= 4 13 = 67 × 10 6 ).…”
Section: Benefits Of Synthesizing Tyrnas To the Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammalian cells, AGO1–4 proteins mediate miRNA-dependent translational repression. Moreover, AGO2, and, to a limited extent, AGO3, possess endoribonuclease activity, which can catalyze smRNA-directed ribonucleolytic cleavage of target mRNAs [ 41 , 42 , 43 ].…”
Section: The Functional Role Of Ago Proteins In Riscmentioning
confidence: 99%